2021
DOI: 10.3390/ani11123347
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Heat Shock Protein 70 Addition in the Culture Medium on the Development and Quality of In Vitro Produced Heat Shocked Bovine Embryos

Abstract: The aims of the present study were to examine the effects of HSP70 addition in the in vitro culture medium of day 3 embryos on their developmental competence and quality. Bovine oocytes (n = 1442) were in vitro matured, inseminated and cultured for the first two days according to standardized methods. The presumptive zygotes were randomly allocated in three experimental groups: Control, C (embryos cultured at 39 °C throughout the culture period), group C41 (temperature was raised to 41 °C from the 48th to 72nd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…The HSP70-primed embryos developed into blastocysts in a significantly higher proportion compared to the non-primed controls. However, they still they lagged behind compared to the non-stressed controls [181]. In conjunction with the findings on the effect of HS on the maturing oocyte, these findings are indicative of two phenomena: first, the endogenous synthesis of HSPs is not sufficient for the early embryo to withstand thermal stress, and second, interventions during oocyte maturation stages are more efficient and appear to persist until the blastocysts stage.…”
Section: Early Embryosmentioning
confidence: 51%
See 2 more Smart Citations
“…The HSP70-primed embryos developed into blastocysts in a significantly higher proportion compared to the non-primed controls. However, they still they lagged behind compared to the non-stressed controls [181]. In conjunction with the findings on the effect of HS on the maturing oocyte, these findings are indicative of two phenomena: first, the endogenous synthesis of HSPs is not sufficient for the early embryo to withstand thermal stress, and second, interventions during oocyte maturation stages are more efficient and appear to persist until the blastocysts stage.…”
Section: Early Embryosmentioning
confidence: 51%
“…Nevertheless, there is an agreement that the further developmental competence of these oocytes is seriously affected, as blastocyst formation rates from heat stressed oocytes are significantly suppressed. After exposure of COCs to increased temperature during in vitro maturation, a reduced embryo yield has been reported in many studies [18,54,[179][180][181][182]. In most of these studies, the heat exposure lasted for 12 to 24 h. We have shown that only six hours exposure (from the second to the eighth hour of IVM) of in vitro matured COCs to 41 • C is sufficient to cause significant reduction in cleavage and blastocyst formation rates [54].…”
Section: The Oocyte and The Surrounding Cumulus Cells (Cocs)mentioning
confidence: 67%
See 1 more Smart Citation
“…A study conducted on dairy cattle by Cai et al [54] revealed that cattle with AC genotype expressed more HSP70 mRNA at 37.5 °C and showed lower levels of apoptosis in lymphocytes of peripheral blood. The effect may occur because HSP repairs proteins and inhibits apoptosis in damaged cells by preventing caspase 3 activation and reducing cellular protein synthesis [55,56]. In addition, single nucleotide polymorphisms (SNPs) (g.895 C/-and g.1128 G/T) in the 5'-UTR region of inducible HSP70.1 alleviate heat stress response during the exposure to heat stress at 43 °C in lactating Holstein cows [57].…”
Section: Heat Shock Protein 70 Polymorphism and Livestock Performancementioning
confidence: 99%